Structural and behavioral determinants of HIV among Indonesian MSM - Neila Sulung; Adi Cahya Murfi; Efriza Efriza; Nurdin Nurdin; Cici Apriza Yanti (International Journal of Public Health Science (IJPHS), 2026)
HIV prevalence among men who have sex with men (MSM) remains disproportionately high in Indonesia. While behavioral risk factors have been widely studied, evidence integrating structural determinants remains limited. This study examined the role of structural and behavioral factors associated with HIV status among MSM in Jambi City, Indonesia. A cross-sectional study was conducted among 60 MSM recruited using non-probability sampling due to the hidden nature of the population. Data were collected using validated structured questionnaires and analyzed using multivariable logistic regression. Fifty percent of respondents were HIV-positive. Low educational attainment emerged as an independent structural determinant of HIV status (AOR = 5.51; 95% CI: 1.14-26.49), whereas behavioral factors showed significant crude associations but lost significance after adjustment. HIV vulnerability among MSM is shaped by structural inequalities beyond individual behaviors. Structural-focused interventions are essential to strengthen HIV prevention strategies in Indonesia.